Transcriptomic profiles of poplar (Populus simonii × P. nigra) cuttings during adventitious root formation - Yu, Yue; Meng, Nan; Chen, Song; Zhang, Hongjiao; Liu, Zhijie; Wang, Yiran; Jing, Yanan; Wang, Yuting; Chen, Su (Frontiers in Genetics, 2022)
The formation of adventitious roots (ARs) is vital for vegetative propagation of poplars. However, the relevant mechanisms remain unclear. To reveal the underlying molecular mechanism, we used RNA-seq to investigate the transcriptional alterations of poplar cuttings soaked in water for 0, 2, 4, 6, 8 and 10 d, respectively. 30,909 genes were differentially expressed in at least one time point. 3,798 were differentially expressed at all the time points, including 2,448 up-regulated and 1,350 down-regulated genes. Biological processes including “cell cycle”, “photosynthesis”, “regulation of hormone levels” and “auxin transport” were enriched in the differentially expressed genes (DEGs). KEGG results showed that the common DEGs were most enriched in pathway of “Carbon fixation in photosynthetic organisms” and “Starch and sucrose metabolism”. We further dissected 38 DEGs related to root and auxin, including 2 lateral root primordium 1 (LRP1), 1 root meristem growth factor (RGF9), 1 Auxin-induced in root (AIR12), 3 rooting-associated genes (AUR1 and AUR3), 8 auxin transcription factors (ARFs and LBDs), 10 auxin respective genes (SAURs and GH3s), 9 auxin transporters (PINs, ABCs, LAX2 and AUXs) and 4 auxin signal genes (IAAs and TIR1). We found that the rooting abilities of poplar cuttings with and without leaves are different. By applying different concentrations of IBA and sucrose to the top of cuttings without leaves, we found that 0.2 mg/mL IBA and 2 mg/mL sucrose had the best effect on promoting ARs formation. The transcriptome results indicated photosynthesis may influence ARs formation in poplar cuttings with leaves and revealed a potential regulatory mechanism of leafy cuttage from poplar cuttings. In addition, we provided a new perspective to resolve rooting difficulties in recalcitrant species.